The Cullin3–Ring E3 ubiquitin ligase complex and USP14 regulate spastin-mediated microtubule severing and promotion of neurite outgrowth - Zhenbin Cai; Hui Wu; Tao Jiang; Ao Ma; Zhichao Meng; Jiehao Zhu; Hongsheng Lin; Yaozhong Liang; Guowei Zhang; Minghui Tan (Neural Regeneration Research)
Post-translational modification of spastin enables precise spatiotemporal control of its microtubule severing activity. However, the detailed mechanism by which spastin turnover is regulated in the context of neurite outgrowth remains unknown. Here, we found that spastin interacted with ubiquitin and was significantly degraded by K48-mediated poly-ubiquitination. Cullin3 facilitated spastin degradation and ubiquitination. RING-box protein 1, but not RING-box protein 2, acted synergistically with Cullin3 protein to regulate spastin degradation. Overexpression of Culin3 or BRX1 markedly suppressed spastin expression, and inhibited spastin-mediated microtubule severing and promotion of neurite outgrowth. Moreover, USP14 interacted directly with spastin to mediate its de-ubiquitination. USP14 overexpression significantly increased spastin expression and suppressed its ubiquitination and degradation. Although co-expression of spastin and USP14 did not enhance microtubule severing, it did increase neurite length in hippocampal neurons. Taken together, these findings elucidate the intricate regulatory mechanisms of spastin turnover, highlighting the roles of the Cullin-3–Ring E3 ubiquitin ligase complex and USP14 in orchestrating its ubiquitination and degradation. The dynamic interplay between these factors governs spastin stability and function, ultimately influencing microtubule dynamics and neuronal morphology. These insights shed light on potential therapeutic targets for neurodegenerative disorders associated with spastin defects.